PENGARUH METODE PEMBELAJARAN DEMONSTRASI TERHADAP KETERAMPILAN BERMAIN BOLA VOLI SISWA DI SMPN 1 BATU BERSURAT - Mimi Yulianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Based on observations of researchers in the field is seen that the method used by the teacher of PE in the communication of lesson material that using conventional methods. The purpose of this study was to determine the effect of learning methods demonstration of the skills of playing volleyball SMPN 1 Batu Bersurat used type of approach to quantitative analysis through test volleyball ground level. This research is a quasi experimental, and the study population was all students of SMPN 1 Batu Bersurat totaling 15 people, while the sampling technique in this study using total sampling technique. then the sample in this study amounted to 15 people. The instrument used was a test volleyball basic level French-Cooper. The data analyzed in this study is data derived from experimental studies that use the pre-test and post-test one group design. Data analysis results show that: the influence of methods of demonstration against playing volleyball skills student at SMPN 1 Batu Bersurat with the results of the statistical count tcount 33.12> ttabel 23.7.